Rates of self‐reported 'burnout' and causative factors amongst urologists in Ireland and the UK: a comparative cross‐sectional study. (30th July 2015) - O'Kelly, Fardod; Manecksha, Rustom P.; Quinlan, David M.; Reid, Alex; Joyce, Adrian; O'Flynn, Kieran; Speakman, Mark; Thornhill, John A.
Abstract : Objectives: To determine the incidence of 'burnout' among UK and Irish urological consultants and non‐consultant hospital doctors (NCHDs). The second objective was to identify possible causative factors and to investigate the impact of various vocational stressors that urologists face in their day‐to‐day work and to establish whether these correlate with burnout. The third objective was to develop a new questionnaire to complement the Maslach Burnout Inventory (MBI), more specific to urologists as distinct from other surgical/medical specialties, and to use this in addition to the MBI to determine if there is a requirement to develop effective preventative measures for stress in the work place, and develop targeted remedial measures when individuals are affected by burnout. Subjects and methods: A joint collaboration was carried out between the Irish Society of Urology (ISU) and the British Association of Urological Surgeons (BAUS). Anonymous voluntary questionnaires were sent to all current registered members of both governing bodies. The questionnaire comprised two parts: the first part encompassed sociodemographic data collection and identifying potential risk factors for burnout, and the second used the MBI to objectively assess for workplace burnout. To evaluate differences in burnout, 2 × 2 contingency tables and Fischer's exact probability tests were used. Results: In all, 575 urologists responded to the online survey out of a total of 1380 invites, yielding a 42% response rate. All respondents were aged <75 years (median age 45 years), with men representing 87.5% of respondents. In all, 75% of respondents worked in England, followed by the Republic of Ireland (9%), Scotland (8%), Northern Ireland (4%), and Wales (3%). In all, 79% of respondents were consultants, with 13% representing training posts, and 40% of respondents held a professorship/clinical lead position. Respondents' countries of origin included England, Scotland, Ireland, India, Wales, Malaysia, Pakistan and Sri Lanka. Overall, the mean emotion exhaustion (EE) score was 23.5, representing a moderate level of EE. The mean depersonalisation (DP) score was 8.2, representing a moderate level of DP. The mean personal achievement (PA) score was 17.1, representing high levels of PA. In all, 86 respondents (15%) reported self‐medication with non‐prescription drugs or alcohol to combat signs and symptoms of burnout, while 46 (8%) sought professional help for symptoms of burnout. In all, 460 respondents (80%) felt that burnout should be evaluated amongst members of the ISU/BAUS, and 345 (60%) would avail of counselling if provided. Conclusions: This is the first study to address the issue of burnout across two separate health systems in the UK and Ireland. This study has shown previously undescribed high levels of burnout characterised by EE and DP, with associated significant levels of self‐medication amongst a male‐predominant cohort. Burnout was attributed to non‐surgical administrative/institutional factors, with most respondents reporting support for staff evaluation and the provision of counselling services. This pilot study lends itself to the creation of risk stratification for urologists, and an opportunity to provide educational resources, training/development programmes, and collegial and administrative support pathways.